THE MEANING OF HALAL CERTIFICATION FOR BUSINESS ACTORS (SMES) IN THE FOOD SECTOR AS A DRIVING FACTOR FOR COMPLIANCE WITH LAW NO. 33 OF 2014 (International Conference on Social and Islamic Studies, 2022)
The halal industry is a very developed sector in recent years, quite a lot of countries are competing to be able to exist in this industry, including Indonesia. Halal certification mandated by Law No. 33 of 2014 is actually an effort by Indonesia to be part of it as well as the key to entering this industry. As a country with Muslim-majority citizens, halal certification should not be difficult but in reality, until now there are still more products that have not been certified halal than products that already have halal certificates, especially in the food sector (food and beverages). Of course, this is interesting to study how the community, especially Small Micro Enterprises (MSEs) are concerned about halal certification. This becomes important because someone does something depending on how someone means to do it. To find out how MSE means a halal certification, this study uses a qualitative research design where data mining is done through interviews and documentation. The results of this study concluded that there is a classification of MSE meaning halal certification, namely the first MSE that states that halal certification is its religious obligation, therefore even if the government does not require it through the law, this halal certification is a necessity that must be done. Second, MSEs believe that halal certification is important for their business, namely that it can expand market expansion and increase their income so that they certify their halal products for the benefit of the economy. Third, MSEs who understand that this halal certificate is a trend must be followed because of the law's encouragement. Therefore, this MSE certifies its halal products because there is a grant from the relevant agency for the halal certification process.   Keywords: MSE, Halal certificate